PENGARUH DISIPLIN KERJA, GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN KONAWE - Heriswanto (FEB Universitas Lakidende, 2020)
This research aims to determine the influence of work discipline, leadership style and organizational commitment to the performance of employees of konawe district' labor and transmigration office. The population in this study was all civil servants in the Konawe County Labor and Transmigration Department, the withdrawal of samples using saturated sample techniques so that the study sample numbered 46 respondents. The method of analysis used in this study is multiple linear regression analysis. The results of this study showed that the variables of work discipline have no effect on employee performance, while the leadership style variables and organizational commitments affect employee performance in the Konawe District Labor and Transmigration Office